The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jcu.22034
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of femoral‐facial syndrome: Case report

Abstract: Femoral-facial syndrome (FFS), also known as femoral hypoplasia-unusual facies syndrome, is a rare condition characterized by a variable degree of unilateral or bilateral femoral hypoplasia associated with facial anomalies. This report describes a case of FFS diagnosed after 13 weeks of pregnancy following the detection of severe micrognathia and bilateral shortening of the femur in the fetus of a patient with DM. The sonographic evolution from the first trimester until birth is described. The clinical finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Sixty‐six individuals were excluded for the following reasons: Twenty‐one patients did not meet the inclusion criteria, either because they had no characteristic facies (Acker, [Patients 1 and 2]; Assemany, Muzzo, & Gardner, ; Burn, Winter, Baraitser, Hall, & Fixsen, [Patient 4]; Caglayan, Gumus, Yikilmaz, Gumus, & Per, ; Chalbaud, Guerrero, Olavarria, & Padilla, ; Ellis, ; Holmes, ; Katdare, ; Lord & Beighton, [Patients 2 and 4]; Mital, Masalawalla, & Desai, ; Tadmor et al, ; Williamson, 1970 [Patients 2, 3, and 4]), or because they did not have the required lower limb involvement (Castro, Peraza, & Zapata, ; Johnson & Sandison, ; Korkmaz et al, ; Russell & Escobar, ; Williamson, [Patient 1]). Three patients presented a distinct phenotypic pattern suggestive of an alternative diagnosis (Depalma, Duray, & Popeo, ; Gupta, Khatri, Agarwal, & Gupta, ; Verma, Jain, & Jain, ). They presented different anomalies such as fracture of long bones, imperforate anus, bladder anomalies (Depalma et al, ), encephalocele (Verma et al, ), and meningoencephalocele, heart defect and preaxial limb reduction defects (Gupta et al, ), the first two in the absence of karyotype information. Twenty‐nine patients were reported without sufficient information to confirm their diagnosis (Apte, Attarde, Patil, Dahiphale, & Ahirrao, ; Burn et al, [Patient 3]; Cuillier, Carasset, Lemaire, Deshayes, & Alessandri, ; Filly, Robnett‐Filly, & Filly, ; Herreros & Franco, ; Holthusen, [Patient 2]; Inati, Nores, Breg, & Petty, [Patients 1 and 2]; Iohom, Lyons, & Casey, ; Kastanek & Michael, ; Lord & Beighton, [Patients 3, 5–9]; Luisin et al, [Patients 1 and 2]Maisels & Stilwel, [Patients 1 to 3]; McCracken, ; Nowaczyk, Huggins, Fleming, & Mohide, [Patient 3]; Pryde, Zelop, & Pauli, ; Singh, Chandra, Mandal Ravi, & Kumari, ; Urban, Ramus, Stannard, & Rogers, ; Vecchio, Salzano, Vecchio, Di Filippo, & Roccella, ; WooSuk & Song, ; Zierei...…”
Section: Resultsmentioning
confidence: 99%
“…Sixty‐six individuals were excluded for the following reasons: Twenty‐one patients did not meet the inclusion criteria, either because they had no characteristic facies (Acker, [Patients 1 and 2]; Assemany, Muzzo, & Gardner, ; Burn, Winter, Baraitser, Hall, & Fixsen, [Patient 4]; Caglayan, Gumus, Yikilmaz, Gumus, & Per, ; Chalbaud, Guerrero, Olavarria, & Padilla, ; Ellis, ; Holmes, ; Katdare, ; Lord & Beighton, [Patients 2 and 4]; Mital, Masalawalla, & Desai, ; Tadmor et al, ; Williamson, 1970 [Patients 2, 3, and 4]), or because they did not have the required lower limb involvement (Castro, Peraza, & Zapata, ; Johnson & Sandison, ; Korkmaz et al, ; Russell & Escobar, ; Williamson, [Patient 1]). Three patients presented a distinct phenotypic pattern suggestive of an alternative diagnosis (Depalma, Duray, & Popeo, ; Gupta, Khatri, Agarwal, & Gupta, ; Verma, Jain, & Jain, ). They presented different anomalies such as fracture of long bones, imperforate anus, bladder anomalies (Depalma et al, ), encephalocele (Verma et al, ), and meningoencephalocele, heart defect and preaxial limb reduction defects (Gupta et al, ), the first two in the absence of karyotype information. Twenty‐nine patients were reported without sufficient information to confirm their diagnosis (Apte, Attarde, Patil, Dahiphale, & Ahirrao, ; Burn et al, [Patient 3]; Cuillier, Carasset, Lemaire, Deshayes, & Alessandri, ; Filly, Robnett‐Filly, & Filly, ; Herreros & Franco, ; Holthusen, [Patient 2]; Inati, Nores, Breg, & Petty, [Patients 1 and 2]; Iohom, Lyons, & Casey, ; Kastanek & Michael, ; Lord & Beighton, [Patients 3, 5–9]; Luisin et al, [Patients 1 and 2]Maisels & Stilwel, [Patients 1 to 3]; McCracken, ; Nowaczyk, Huggins, Fleming, & Mohide, [Patient 3]; Pryde, Zelop, & Pauli, ; Singh, Chandra, Mandal Ravi, & Kumari, ; Urban, Ramus, Stannard, & Rogers, ; Vecchio, Salzano, Vecchio, Di Filippo, & Roccella, ; WooSuk & Song, ; Zierei...…”
Section: Resultsmentioning
confidence: 99%
“…6 Most studies report on the diagnosis of micrognathia on prenatal sonography during the second and third trimester [7][8][9][10] ; however, with adequate ultrasound operator awareness, experience and skill, micrognathia is potentially detectable in the first trimester. 5,[11][12][13] A previous ultrasonographic study established reference ranges for fetal facial profile markers during the first trimester in a Chinese population. 14 To the authors' knowledge, no ultrasonographic study has developed a dedicated protocol that provides objective criteria for the early detection of abnormalities of the mandible at 11-13 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies report on the diagnosis of micrognathia on prenatal sonography during the second and third trimester 7–10 ; however, with adequate ultrasound operator awareness, experience and skill, micrognathia is potentially detectable in the first trimester 5,11–13 . A previous ultrasonographic study established reference ranges for fetal facial profile markers during the first trimester in a Chinese population 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The severity of this condition appears to vary widely among reported cases and there is little evidence regarding the prognosis of FFS. While survival can be normal (Castro et al, 2014), deaths within a few hours to months after birth have been reported (Luisin et al, 2017). There is little information on patients with this condition in adulthood (Nowaczyk et al, 2010).…”
Section: Introductionmentioning
confidence: 99%